2011
DOI: 10.1093/aob/mcr086
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms for aerenchyma formation in leaf sheaths of rice genotypes displaying a quiescence or escape strategy for flooding tolerance

Abstract: While ethylene controls aerenchyma formation in the fast-elongating 'Arborio Precoce' variety, in 'FR13A' ROS accumulation plays an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 57 publications
1
63
0
5
Order By: Relevance
“…ROS that cause oxidative stress include hydrogen peroxide (H2O2), peroxidase "POD" decompose H2O2, also suggests that POD is involved in fine regulation of H2O2 level (Mittler 2002). Parlanti et al (2011) reported that two rice varieties, 'FR13A' and 'Arborio Precoce', showed different responses to Environment, Earth and Ecology Vol. 1 No.…”
Section: Discussionmentioning
confidence: 99%
“…ROS that cause oxidative stress include hydrogen peroxide (H2O2), peroxidase "POD" decompose H2O2, also suggests that POD is involved in fine regulation of H2O2 level (Mittler 2002). Parlanti et al (2011) reported that two rice varieties, 'FR13A' and 'Arborio Precoce', showed different responses to Environment, Earth and Ecology Vol. 1 No.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, lysigenous cortical aerenchyma form constitutively in roots, even in well-drained soils, and in older internodes at the base of the culm (Steffens et al, 2011). Although aerenchyma formation was not directly linked to submergence tolerance in rice (Parlanti et al, 2011), it is important for waterlogging tolerance and may augment underwater photosynthesis and oxygen diffusion to the root system. In fact, some species with constitutive aerenchyma further improve aeration during waterlogging, as evidenced by the expansion of constitutively formed aerenchyma toward the tip of adventitious roots during flooding in a waterlogging-tolerant teosinte (Zea nicaraguensis; Abiko et al, 2012).…”
Section: Morphological and Anatomical Adaptations That Increase Floodmentioning
confidence: 99%
“…Aerenchyma: Airing the Plant Aerenchymatous tissue can develop in both roots and shoots depending on the species and environmental conditions (Colmer and Pedersen, 2008;Parlanti et al, 2011;Steffens et al, 2011). These airfilled breaches extending throughout the inner plant connect flooded parts with those still in aerial contact and greatly improve internal aeration.…”
Section: Ethylene-mediated Flooding-adaptive Traitsmentioning
confidence: 99%
“…ACC treatment only on one side resulted in a higher percentage of aerenchyma in the ACC-exposed developing root, whereas 1-methylcyclopropane (an ethylene perception inhibitor) elicited a reverse trend (Yukiyoshi and Karahara, 2014). The ethylene dependency and inducibility of aerenchyma formation can strongly vary between genotypes (Parlanti et al, 2011;Yin et al, 2013). For example, the rice varieties FR13A and Arborio Precoce both show constitutive aerenchyma in leaf sheaths that is further enhanced by submergence.…”
Section: Ethylene-mediated Flooding-adaptive Traitsmentioning
confidence: 99%